Front Matter (Journal of the Assembly for Expanded Perspectives on Learning, 1998)
Editor's Message We live in a culture dominated by boundaries of all sorts. Personal space is precious to us, and we become uneasy when others do not honor those invisible borders, ignoring, perhaps, the ways in which those borders shift with age, class, gender, and ethnicity. We have office doors, house doors, and bedroom doors that we close and lock. Many of us demarcate a sharp separation between private life and public work, arguing, as does Michael Bèrubé that the life lived has nothing to do with the work written. And so we exist, being careful not to overstep our "boundaries," communicating in body language and in words the necessity of distance between me and thee, spirit and school, body and mind. Much that we do in AEPL is designed to disrupt those boundaries, to resist the ways in which arbitrary separations lock us into damaging patterns of living, thinking, and feeling. We believe, as Gregory Bateson says, that severing mind from body will result in an epistemological error that will surely hurt us. Thus, in our workshops at professional sites, in our annual conference in the Colorado Rockies, and in our interactions throughout the year—many of which are carried on in cyberspace—we celebrate the necessary unity of mind, spirit, and body. This issue of our first jointly edited JAEPL continues that celebration by featuring articles addressing in varied fashion our necessary unity. Laurence E. Musgrove in "Attitudes Toward Writing" focuses on ways in which teachers must attend to the importance of students' attitudes while writing. Mark McBeth in "Body Oddities" blurs the boundaries between exposition and fiction, as well as between flesh and word, as he plumbs the ways in which differences in body encode differences in being, underlining the organizing and disruptive nature of bodies. Focusing on the needs of the spirit, Hildy Miller argues from a feminist perspective for the importance of a goddess religion for the development of women in our patriarchal culture. Keith Rhodes blurs the boundaries that separate imagination and rationality that have become solidified in Western culture. Using the Jungian archetype of the trickster, he re-reads Plato and Gorgias as philosopher-rhetoricians embued with a subtle resistance to absolute rationality that marks the trickster. Judy Halden-Sullivan in "Reflection and an Appetite for Experience" taps the work of Hans-Georg Gadamer to argue that the synthesis of experience and reflection is essential for our composition classrooms. Finally, in "The Healing Power of Words" Dave Waddell highlights the reciprocity of language, body, and spirit, illustrating how each mutually infuses the other. Each article, separately and jointly, offers unique insight on the necessary unity of mind, spirit, and body. We also wish to acknowledge the work of our Book Review Editor, Anne Mullin, who, after a three-year tenure in office, will be turning her efforts to new projects. We welcome Susan Blau as the incoming Book Review Editor, and eagerly anticipate the upcoming array of reviews. We also wish to welcome Jane Tompkins to the Executive Committee as ex officio member, Alice G. Brand to the Advisory Board, and Tom Dean to the editorship of the AEPL Newsletter. Judy Arnold, outgoing Newsletter editor, will be pursuing other writing projects. Breaking with tradition, we have chosen to issue an open call for the fifth issue of JAEPL. Rather than focusing on a specific topic or theme, we invite submissions on any topic or approach that offers insight into AEPL interests. We also begin a new tradition in that we will be using MLA (4th edition), rather than APA, citation style. Please visit our website at http://www.bsu.edu/english/publications/jaepl/ and e-mail us all your comments and suggestions. We look forward to introducing new discourse and new topics to the world of cyberspace.